Copper/Silver Cocatalyzed Regioselective C5–H Functionalization of 8-Aminoquinoline Amides with 1,3-Dicarbonyl Compounds - Zhan, Fuxu; Zhang, Wei; Zhao, Huaiqing (Synthesis, 2020)
A copper/silver co-catalyzed cross-dehydrogenative coupling reaction is developed to achieve exclusively remote C5–H coupling of 8-aminoquinoline amides with the methylenic sp3 C–H bond of 1,3-dicarbonyl compounds. This protocol provides a highly regioselective synthetic route for the functionalization of 8-aminoquinoline amides at C5 under mild conditions. Preliminary experiments reveal that radicals may be involved in this catalytic transformation.
Keywords: copper; silver; 8-aminoquinoline amides; 1,3-dicarbonyl compounds; C5–H functionalization